2010
DOI: 10.1118/1.3425789
|View full text |Cite
|
Sign up to set email alerts
|

Verification of MLC based real‐time tumor tracking using an electronic portal imaging device

Abstract: Purpose:The authors have developed a novel technique using an electronic portal imaging device ͑EPID͒ to verify the geometrical accuracy of delivery of dose-rate-regulated tracking ͑DRRT͒. This technique, called verification of real-time tracking with EPID ͑VORTE͒, can potentially be used for both on-line and off-line quality assurance ͑QA͒ of MLC-based dynamic tumor tracking. Methods: The shape and position of target as a function of time, which is assumed to be known, is projected onto the EPID plane. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In image-guided radiotherapy systems (IGRT), either the aperture of the radiation beam [1][2][3][4][5][6][7][8][9][10] or the patient couch 11 can be adjusted to match the detected tumor motion. The Cyber-Knife 12 radiosurgery system (Fig.…”
Section: A the Need For Prediction During Adaptive Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…In image-guided radiotherapy systems (IGRT), either the aperture of the radiation beam [1][2][3][4][5][6][7][8][9][10] or the patient couch 11 can be adjusted to match the detected tumor motion. The Cyber-Knife 12 radiosurgery system (Fig.…”
Section: A the Need For Prediction During Adaptive Radiotherapymentioning
confidence: 99%
“…Tracking with gantry-mounted linear accelerators has been limited to research using phantoms. [2][3][4][5][6][7][8][9][10] In most of these studies, system latency due to image acquisition, image saving and reading, tumor detection and aperture adjustment has been identified as one of the challenges for real-time adaptive treatment. 6 Latencies ranging from 50 to 1400 ms have been reported.…”
Section: A the Need For Prediction During Adaptive Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Moreover, linear accelerator (linac) rotation can affect gantry-mounted accessories such as the electronic portal imaging device (EPID), since the EPIDsupporting arm is not mechanically perfect and rigidly attached. With the growing application of EPIDs in preand post-treatment dosimetry verification, [10][11][12][13][14][15] realtime dosimetry verification 16,17 and real-time tumour tracking for intrafraction motion management in modern radiotherapy, [18][19][20] it is essential to characterize and account for the mechanical system imperfections of linacs.…”
Section: Conclusion and Advances In Knowledgementioning
confidence: 99%
“…In support of this idea, the continuous dose imaging of exit radiation by EPID was recently demonstrated with sufficient dosimetric accuracy by McCurdy and Greer. 23 Han-Oh et al 24 demonstrated the feasibility of using EPID images to determine the geometrical accuracy of tumor tracking treatment with a moving MLC system.…”
Section: Introductionmentioning
confidence: 99%